Secondary School Students’ Responses on The Use of Youtube Shorts-Microsoft Co-pilot AI Collaboration in English Grammar Learning: A Craap-Based Perspective - Muhammad Rafli Nugraha; Nur Aeni; Muhalim Muhalim (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study investigates secondary school students’ responses to the integration of YouTube Shorts and Microsoft Copilot AI in English grammar learning, assessed through the CRAAP (Currency, Relevance, Authority, Accuracy, Purpose) model. Motivated by students’ declining interest in grammar and the limitations of traditional instructional methods, this research explores the pedagogical potential of combining short-form educational videos with AI-driven chatbots. Utilizing a quantitative descriptive approach, a CRAAP-based questionnaire was administered to a purposively selected Grade VIII class at UPT SMPN 33 Makassar following an AI-enhanced grammar learning intervention focusing on parts of speech and tenses. Results from 29 respondents revealed highly positive perceptions across all five CRAAP dimensions, with every statement receiving a “Strongly Agree” rating above 75%. Currency and Relevance emerged as the most endorsed aspects, while Authority and Purpose, though still positively rated, suggested the need for clearer source attribution. The findings indicate that the YouTube Shorts–Microsoft Copilot AI collaboration not only effectively supports grammar comprehension but also aligns with students’ digital preferences and fosters learner autonomy. This study affirms the value of integrating multimedia and AI in language education and encourages future efforts to enhance credibility, transparency, and long-term engagement with such tools.Keywords: English grammar learning, student responses, CRAAP model, AI, short video social media, YouTube Shorts, Microsoft Copilot AI.